Determining colour coordinates of colourful light generated by three laser sources. (March 2019) - Isnaeni,; Selvina,; Tahir, D
Abstract: Colourful lighting can be generated using various light sources, such as filament lamps, light emitting diodes (LED), and laser. In this work, we present a simple method to generate colourful lighting using three laser sources (red, green, and blue laser) and quantify the generated colours. We set up several laser sources and directed the entire laser beam onto white dove light bulb. We were able to generate 9 different colours and quantify the colour using modified calculation of colour coordinates of colour space diagram CIE 1931. Our simple calculation of colour coordinates agreed with colour appearance. To validate our method, we conducted a simple survey of 25 respondents. 5 out of 9 generated colours show agreement between our calculation method and survey. Thus our modified calculation method can be used to quantify colour lighting generated using three laser sources.